Peningkatan Hasil Belajar Siswa Menggunakan Model PBL Pada Materi Mewartakan Kerajaan Allah Melalui Pribadi Yesus - Selpriani Selpriani (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Selpriani, 2023. The issue of equal education is an issue that has been addressed by various countries to improve the quality of human life. However, the approach that has been taken so far emphasizes the point of view that equality education is an effort to resolve the residue of formal education. This view in current conditions is no longer appropriate, because advances in information and communication technology make it possible for people to learn anytime and anywhere. The position of equal education must be on par with formal education, that is, they both provide services for the educational rights of citizens. This is in line with the mandate of the Indonesian constitution, that every citizen has the right to education. It is hoped that PBL with the help of audio visuals can reveal 1) How students' learning outcomes improve on the material of proclaiming the kingdom of God through the person of Jesus, 2) What are the inhibiting and supporting factors for increasing student learning outcomes on the material of proclaiming the kingdom of God through the person of Jesus, 3) What efforts are being made by Catholic religious education teachers to overcome obstacles in improving student learning outcomes using material proclaiming the kingdom of God through the person of Jesus. This Class Action Research Report aims to 1) To improve student learning outcomes using problem based learning on the material of proclaiming the kingdom of God through the person of Jesus, 2) To find out the inhibiting and supporting factors in improving student learning outcomes using problem based learning on the material of proclaiming the kingdom of God through the person Jesus, 3) To determine the efforts that can be made by Catholic Religious Education Teachers to overcome obstacles in improving student learning outcomes using the problem based learning model on the material of proclaiming the kingdom of God through the person of Jesus. The object of the research is that Problem Based Learning (PBL) assisted by audio visuals can improve student learning outcomes. The form of this research is classroom action research with a cyclical model, each cycle consists of four stages, namely, planning, implementing actions, observing and reflecting. At the observation stage, the researcher collects data by observing student activities guided by the Pancasila Student Profile rubric (P3) through the use of the Problem Based Learning (PBL) Model with audio visual assistance. The observation results from 13 students in Cycle I averaged 69.5%, and in Cycle II increased to an average of 82.13%. From this increase, it can be seen that it is 12.73% higher than before.